Parasites in cultured and feral fish - Scholz, T (Veterinary parasitology, 1999)
Parasites, causing little apparent damage in feral fish populations, may become causative agents of diseases of great importance in farmed fish, leading to pathological changes, decrease of fitness or reduction of the market value of fish. Despite considerable progress in fish parasitology in the last decades, major gaps still exist in the knowledge of taxonomy, biology, epizootiology and control of fish parasites, including such 'evergreens' as the ciliate Ichthyophthirius multifiliis, a causative agent of white spot disease, or proliferative kidney disease (PKD), one of the most economically damaging diseases in the rainbow trout industry which causative agent remain enigmatic. Besides long-recognized parasites, other potentially severe pathogens have appeared quite recently such as amphizoic amoebae, causative agents of amoebic gill disease (AGD), the monogenean Gyrodactylus salaris which has destroyed salmon populations in Norway, or sea lice, in particular Lepeophtheirus salmonis that endanger marine salmonids in some areas. Recent spreading of some parasites throughout the world (e.g. the cestode Bothriocephalus acheilognathi) has been facilitated through insufficient veterinary control during import of fish. Control of many important parasitic diseases is still far from being satisfactory and further research is needed. Use of chemotherapy has limitations and new effective, but environmentally safe drugs should be developed. A very promising area of future research seems to be studies on immunity in parasitic infections, use of molecular technology in diagnostics and development of new vaccines against the most pathogenic parasites.
Keywords: Oncorhynchus mykiss; nemoci ryb; Aquaculture; Helminthiasis, Animal; nemoci ledvin; ryby; Fish Diseases; helmintózy zvířat; Parasitic Diseases, Animal; amébiáza; Amoeba; losos; parazitární nemoci u zvířat; zvířata; Eukaryota; Crustacea; Protozoan Infections, Animal; Salmon; Hymenostomatida; cizopasní červi; Fishes; Amebiasis; Helminths; korýši; vodní hospodářství; Animals; protozoální infekce zvířat; Kidney Diseases